Longitudinal inter-relations between school cultural socialization and school engagement: The mediating role of school climate. (October 2021) - Del Toro, Juan; Wang, Ming-Te
Abstract: The question of whether schools should promote cultural pride and engage students in ethnic traditions is hotly contested. To contribute to this debate, this longitudinal study examined whether school cultural socialization predicted adolescents' engagement in school over time and whether this relation was mediated by school climate. Data were collected in four waves during a two-year period from 254 African American fifth-graders (53.9% males; M age  = 10.95 at Wave 1) enrolled in three public middle schools. Results revealed that African American youth who reported more school cultural socialization also had greater school engagement over time. This longitudinal relation was fully mediated by youth's perceptions of school climate. Implications for how to promote African American youth's perceptions of schools as culturally sensitive and supportive environments are discussed. Highlights: School cultural socialization are school-based lessons about students' races. Youth perceiving more cultural socialization reported greater engagement in school. Positive school climate perceptions mediated the aforementioned link. Implications include how to promote perceptions of schools as supportive contexts.